Áreas verdes urbanas, imagem e uso: um estudo geográfico sobre a cidade de Maringá – PR - Bovo, Marcos Clair [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
A manutenção das áreas verdes urbanas sempre foi justificada pelo seu potencial em proporcionar qualidade ambiental à população. Essas áreas interferem diretamente na qualidade de vida por meio das funções ecológico-ambiental, estética, paisagística, climática, psicológica e também recreativa que elas exercem para amenização das consequências negativas da urbanização. Neste sentido, a presente pesquisa tem por objetivo caracterizar e analisar as áreas verdes urbanas de Maringá/PR, destacando seus aspectos paisagísticos e sua infraestrutura a fim de compreender a qualidade ambiental desses espaços públicos e propor medidas que auxiliem no seu planejamento e gerenciamento. Para tanto, foram realizadas análises investigativas das 104 praças existentes em Maringá, de 09 parques urbanos e de 01 cemitério parque. Para a análise realizou-se trabalho de campo com base em dois formulários. O primeiro deles visava à avaliação qualitativa e quantitativa da vegetação e se constituiu dos seguintes itens: nome da área verde, sua localização, sua altitude, a vegetação nela existente, o porte e a densidade da vegetação, a cobertura do solo, as condições de relevo, aspectos físicos e sanitários da vegetação, tipo de ocupação das proximidades e qualidade paisagísticas das praças, dos parques e do cemitério parque. O segundo formulário teve como objetivo fazer o levantamento dos aspectos quantitativos e qualitativos dos equipamentos e estruturas existentes em cada logradouro...

The maintenance of urban green areas has always been justified by its potential to provide quality environment for people. These areas directly affect the quality of life through ecological functions, environmental, aesthetic, landscape, climate, psychological and recreational they have for alleviating the negative consequences of urbanization. Accordingly, this research aims to characterize and analyze the areas of urban green Maringá / PR, highlighting the landscape aspects and its infrastructure in order to understand the quality of the environmental public spaces and propose measures to assist in their planning and management. This way, it was investigated for analysis of existing in Maringá, 104 squares,09 parks and 01 cemetery. For the analysis it was carried out the fieldwork in two forms. The first one aimed at qualitative and quantitative assessment of vegetation and consisted of the following: name of the green area, its location, its altitude, the vegetation in that area, the size and density of vegetation, soil cover, the conditions for relief , physical and health of vegetation, type of occupation of the nearby landscape and quality of parks, the parks and the cemetery park. The second form aimed to make the lifting of quantitative and qualitative aspects of equipment and structures in each street addresses. Accordding to the results found the lack of infrastructure and lack of criteria adopted in the spatial distribution of the squares, and the neglect of the public, about the replacement of equipment and facilities to be located in squares, whichever the greater investment in the central part and in the absence periphery. As the squares of the predominant vegetation and tree trick in 49.03%, then, the squares formed by the vegetation... (Complete abstract click electronic access below)
Keywords: Geografia; Solo urbano - Uso; Áreas verdes públicas; Green areas; Squares; Parks; Urban land - Usage and occupancy